A Concept: Ethnopedagogical-Based Character Educational Model of Elementary School Students - Nadila Dirgantari; Isah Cahyani (Publikasi Indonesia, 2023)
This study seeks to provide argumentative information regarding the urgency of implementing an ethnopedagogical-based character educational model to build superior character for elementary school students, to overcome the challenges of character education in an increasingly anomalous and complex globalization era, so that character education can become meaningful and have a real impact on strengthening character superior students. This research was conducted using a qualitative approach, with the literature study method and data analysis. This research has resulted in the form of a superior character vision that leads to moral character and performance character as a representation of citizens who are inspired by the Indonesian nation and an ethnopedagogical-based character educational model that is holistic because, in addition to trying to realize inclusive character education in elementary schools, the integration of efforts to strengthen superior character as well as the preservation of local culture, also strengthened by the example of educators, with not only the concepts and practices of ethnopedagogical-based but also the preservation of local culture, through character building, becoming a civic movement that strengthens the superior character of students in elementary schools. The study results concluded that the ethnopedagogical-based character educational model is adaptive to educational challenges and character learning in the era of globalization, digitalisation, and the industrial revolution 4.0 because it accommodates visions, strategies and efforts to form superior human beings. The character is also consistently based on Pancasila so that Indonesia can reach the peak of its civilization.